2023
DOI: 10.1097/md.0000000000033254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different weight loss dietary interventions on body mass index and glucose and lipid metabolism in obese patients

Abstract: To investigate the effects of different weight loss interventions on body mass index (BMI) and glucose and lipid metabolism in obese patients. Obese patients (n = 135) admitted to our hospital between December 2020 and August 2022 were divided into 3 groups, according to their diet patterns: calorie-restricted diet (CRD) group (n = 39), high-protein diet (HPD) group (n = 28), and 5 + 2 intermittent fasting (IF) group (n = 68). Body weight, body fat rate, BMI, hip circumference, and waist circumference were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
4
1
0
Order By: Relevance
“…Our study was consistent with some previous researches that evaluated the effects of different interventions on the obese individuals and showed significant positive correlation between body weight changes and WC and/or HC 10 20 . A recent study showed that body weight, BMI, WC, and HC decreased significantly after a calorie-restricted high-protein diet, and intermittent fasting 10 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study was consistent with some previous researches that evaluated the effects of different interventions on the obese individuals and showed significant positive correlation between body weight changes and WC and/or HC 10 20 . A recent study showed that body weight, BMI, WC, and HC decreased significantly after a calorie-restricted high-protein diet, and intermittent fasting 10 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study was consistent with some previous researches that evaluated the effects of different interventions on the obese individuals and showed significant positive correlation between body weight changes and WC and/or HC 10 20 . A recent study showed that body weight, BMI, WC, and HC decreased significantly after a calorie-restricted high-protein diet, and intermittent fasting 10 . A significant reduction in body weight and FM was also indicated in obese or overweight subjects after adherence to both Mediterranean diet (MD) and the Very Low-Calorie Ketogenic diet (VLCKD), whereas the MD caused a higher reduction in WC and FM 11 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our current findings, both animal models 37,42 and patient studies [43][44][45] have previously shown that dietary interventions that reduce body weight also improve metabolic disorders, including T2D and its complications. Moreover, we found that all three dietary interventions ameliorated glycemic status, consistent with other reports in db/db mice 46,47 and in patients with T2D.…”
Section: Discussionsupporting
confidence: 91%
“…Since the food intake of the IF-adlib group was similarly reduced to that of the calorie-restricted animals (C-CRD), it explained why the body weight gain of both groups was not different during this experiment. This agrees with the similar body weight loss observed between patients who are obese or overweight when subjected to CRD or IF regimes [ 21 ]; it has also been described that animals [ 22 ] or patients following IF [ 21 ] present less fat percentage than those with CRD when body composition is analyzed.…”
Section: Discussionsupporting
confidence: 89%